2013
DOI: 10.5301/ejo.5000253
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Application of Tissue Adhesives in Corneal Traumas

Abstract: Fibrin glue for the reconstruction of corneal wounds was easier to use than cyanoacrylate glue and caused less glue crust formation on the corneal surface. The speed of polymerization is an important factor. Excessive glue on the cornea was irritating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…One of the challenges with the application of current bioadhesives in ophthalmology is the consistency of the bioadhesive at the time of application. [ 6 ] Specifically, the bioadhesive besides having strong adhesion after polymerization, requires robust cohesion before cross‐linking. If the bioadhesive has a low cohesion (very liquid) it will easily spread over the field to undesired areas before cross‐linking, while if it is too viscous (very high cohesion), it will not adequately spread to provide coverage of the targeted area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the challenges with the application of current bioadhesives in ophthalmology is the consistency of the bioadhesive at the time of application. [ 6 ] Specifically, the bioadhesive besides having strong adhesion after polymerization, requires robust cohesion before cross‐linking. If the bioadhesive has a low cohesion (very liquid) it will easily spread over the field to undesired areas before cross‐linking, while if it is too viscous (very high cohesion), it will not adequately spread to provide coverage of the targeted area.…”
Section: Resultsmentioning
confidence: 99%
“…One of the challenges with the application of current bioadhesives in ophthalmology is the consistency of the bioadhesive at the time of application. [6] Specifically, the bioadhesive besides having strong adhesion after polymerization, requires The fabrication process of light-curable COMatrix (LC-COMatrix) hydrogel. Porcine corneas were decellularized using freeze-thaw method and partially digested with pepsin/HCl cocktail to fabricate thermoresponsive COMatrix hydrogel.…”
Section: Viscosity Characterization and Photogelation Kinetics Of Lig...mentioning
confidence: 99%
See 1 more Smart Citation
“…40 Given this speed of polymerization, it can be difficult to remove excess cyanoacrylate glue, which can result in crusting that is irritating to the patient. 41 In addition, the low viscosity of the glue before polymerization makes inadvertent spread onto the ocular surface difficult to avoid. Cyanoacrylate glue is also not biodegradable and releases toxic bi-products, like formaldehyde, that can cause inflammation, neovascularization, and cytotoxicity, which is not ideal for wound healing.…”
Section: Alternative Methods Of Globe Closure: Contact Lenses and Ocu...mentioning
confidence: 99%
“…Compared to cyanoacrylate, fibrin glue may be less toxic but not as readily available [ 120 ]. Furthermore, a study found fibrin glue to be easier to use than cyanoacrylate glue due to less crust formation on the corneal surface, which can be irritating to the patient [ 124 ]. However, fibrin glue requires a significantly longer time for adhesive plug formation compared to cyanoacrylate adhesive [ 125 ].…”
Section: Mechanical Barrier Therapiesmentioning
confidence: 99%